LRRK2 impairs PINK1/Parkin-dependent mitophagy via its kinase activity: pathologic insights into Parkinson's disease. (9th January 2019) - Bonello, Fiona; Hassoun, Sidi-Mohamed; Mouton-Liger, François; Shin, Yea Seul; Muscat, Adeline; Tesson, Christelle; Lesage, Suzanne; Beart, Philip M; Brice, Alexis; Krupp, Johannes; Corvol, Jean-Christophe; Corti, Olga
Abstract: Mutations of LRRK2, encoding leucine-rich repeat kinase 2 (LRRK2), are the leading cause of autosomal dominant Parkinson's disease (PD). The most frequent of these mutations, G2019S substitution, increases kinase activity, but it remains unclear how it causes PD. Recent studies suggest that LRRK2 modulates mitochondrial homeostasis. Mitochondrial dysfunction plays a key role in the pathogenesis of autosomal recessive PD forms linked to PARK2 and PINK1, encoding the cytosolic E3 ubiquitin-protein ligase Parkin and the mitochondrial kinase PINK1, which jointly regulate mitophagy. We explored the role of LRRK2 and its kinase activity in PINK1/Parkin-dependent mitophagy. LRRK2 increased mitochondrial aggregation and attenuated mitochondrial clearance in cells coexpressing Parkin and exposed to the protonophore carbonylcyanide m-chlorophenylhydrazone. Förster resonance energy transfer imaging microscopy showed that LRRK2 impaired the interactions between Parkin and Drp1 and their mitochondrial targets early in mitophagy. The inhibition of LRRK2 kinase activity by a 'kinase-dead' LRRK2 mutation or with a pharmacological inhibitor (LRRK2-IN-1) restored these interactions. The monitoring of mitophagy in human primary fibroblasts with the novel dual-fluorescence mtRosella reporter and a new hypothermic shock paradigm revealed similar defects in PD patients with the G2019S LRRK2 substitution or PARK2 mutations relative to healthy subjects. This defect was restored by LRRK2-IN-1 treatment in LRRK2 patients only. Our results suggest that PD forms due to LRRK2 and PARK2 mutations involve pathogenic mechanisms converging on PINK1/Parkin-dependent mitophagy.